Determination of Sugars and Humectants in Cigarette by Solid Phase Extraction and Ion Chromatography with Pulsed Amperometric Detection - Zhang, Qunfang; Xue, Jingjiao; Zhong, Jia; Ye, Yanqing; Yang, Guangyu (Asian Journal of Chemistry, 2011)
The determination of sugars and humectants in cigarette by solid phase extraction and ion chromatography with pulsed amperometric detection (IC-PAD) was studied. The sugars (D-glucose, Dfructose, sucrose, D-galactose, maltose) and humectants (dglucitol, xylitol, glycerol, propylene glycol) were extracted from the cigarette samples with water. The extract was purified by solid phase extraction with C18 cartridge and analyzed by ion chromatography with pulsed amperometric detection. The recoveries of this method were ranging from 95-103 %. The relative standard derivation of overall intra-day variations were less than 1.8 % and the relative standard derivation of inter-day variations were less than 2.2 %. The detection limits were ranged from 30-80 ng/mL, respectively, for the different sugars and humectants. Results showed that the IC-PAD method provided a simple and powerful tool for the analysis of sugars and humectants in cigarette.